2016
DOI: 10.1155/2016/5805034
|View full text |Cite
|
Sign up to set email alerts
|

New Collagen-Dextran-Zinc Oxide Composites for Wound Dressing

Abstract: The goal of this paper was the design, development, and characterization of some new composites, based on collagen and dextran as natural polymers and zinc oxide as antimicrobial, to be used in wound healing. Collagen hydrogels with various concentrations of dextran and zinc oxide were investigated in terms of rheological analysis. The spongious composites, obtained by freeze-drying of hydrogels, were evaluated by morphology (SEM), water uptake, and biological (enzymatic biodegradation) analysis. All the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…Moist wounds are known to heal faster due to the adequate supply of growth factors and other molecules to the healing tissues [ 31 ]. Moreover, it helps to keep excessive exudates [ 32 ]. A good swelling ratio is necessary to provide essential nutrients for the cells [ 33 ] and to deliver antibiotics to the wound bed [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moist wounds are known to heal faster due to the adequate supply of growth factors and other molecules to the healing tissues [ 31 ]. Moreover, it helps to keep excessive exudates [ 32 ]. A good swelling ratio is necessary to provide essential nutrients for the cells [ 33 ] and to deliver antibiotics to the wound bed [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the results were strongly influenced by the nature and concentration of composite components. From the obtained results (performances of the hydrogels, stationary rheometry, porous structure, morphology, and biological behavior), it was observed that the composite based on collagen and dextran with 50% ZnO was the most promising for future applications in wound dressing and as a biomaterial with a high potential for skin regeneration [8].…”
Section: Functionalized Collagen Hydrogels For Wound Healing Applicatmentioning
confidence: 99%
“…One of the significant advantages of a rapid bactericidal action may be that it permits wound healing to proceed without bacterial interference and reduces the likelihood for resistance to develop [7]. New composites, based on collagen and nanoparticles, are currently under research to be used for the wound healing [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The rheological measurements were carried out at 37°C±0.5°C. The operational conditions were detailed in our previous studies (Paunica-Panea et al, 2016;Ghica et al, 2012a). The viscosity of the hydrogels was plotted as a function of shear rate and the corresponding curves were obtained.…”
Section: Rheological Analysismentioning
confidence: 99%